Battery explantation after sacral neuromodulation in the medicare population12. Issue 3 (27th July 2012) - Cameron, Anne P.; Anger, Jennifer T.; Madison, Rodger; Saigal, Christopher S.; Clemens, J. Quentin; ,
Abstract Aims To determine sacral neuromodulation battery life and the patient and provider risk factors for early explantation in a population‐based sample. Methods A 5% sample of Medicare beneficiaries from 1997 to 2007 served as the data source. All patients who had a sacral neuromodulation device implanted in that time period were included. Variables included in a multivariate analysis of risk factors for removal included gender, age, race, diagnosis, type of test phase, provider specialty, and volume. The number of device reprogramming events was also recorded in this time period. Results Mean follow‐up was 60.5 months. Patients on average had 2.15 reprogramming episodes in their first year, with that number decreasing over subsequent years. Out of the 558 batteries implanted 63 (11.3%) were explanted. Of the 19 implanted individuals who carried the diagnosis of interstitial cystitis (IC), 11 (57.9%) had the battery removed. This was the only variable that predicted early removal, with an odds ratio of explantation of 10.5 (95% CI: 3.9–28.4). Conclusion Very few sacral neuromodulation batteries, once implanted, are removed prematurely. Patients with IC, however, are at very high risk of requiring premature battery removal. Neurourol. Urodynam. 32: 238–241, 2013. © 2012 Wiley Periodicals, Inc.